The Impact of Ubiquitous Learning Environments on Motivation in English Language Classes - Pierre Biyogho; Maya Nguema; Estelle Ntoutoume (Yayasan Adra Karima Hubbi, 2026)
The increasing integration of digital technologies into education has transformed traditional classrooms into ubiquitous learning environments (ULEs), where learning can occur anytime and anywhere. In English language education, this paradigm shift has the potential to enhance learners’ motivation by fostering autonomy, accessibility, and engagement beyond classroom walls. However, despite the growing adoption of mobile and cloud-based learning systems, empirical evidence on how ubiquitous learning affects students’ motivational dimensions remains limited. This study investigates the impact of ULEs on learners’ intrinsic and extrinsic motivation in English language classes, focusing on how continuous access to resources and interaction influences engagement and self-regulated learning. A quasi-experimental mixed-method design was employed involving 120 high school students from three urban schools in Indonesia. Participants were divided into experimental (ULE-based learning) and control (traditional classroom) groups over a 10-week intervention. Quantitative data were collected through the Motivated Strategies for Learning Questionnaire (MSLQ), while qualitative insights were derived from focus group discussions and digital learning logs. Statistical analysis using ANCOVA revealed a significant increase in intrinsic motivation (F(1,117) = 24.86, p < 0.001) and learner autonomy (F(1,117) = 19.34, p < 0.01) in the experimental group. Qualitative results indicated that flexibility, instant feedback, and collaborative features in ULEs were key factors enhancing engagement. The findings suggest that ubiquitous learning environments can significantly strengthen motivation in English language learning by enabling continuity between formal and informal contexts. The study concludes that ULEs promote learner-centered pedagogy, encouraging sustainable motivation through personalization, mobility, and real-time interaction.